IMPROVEMENT OF TAX CONTROL MECHANISMS IN EXPORT OPERATIONS (American Journal of Research in Humanities and Social Sciences, 2023)
The mechanisms of tax control in export operations, as well as the key determinants of the future macroeconomic environment, distinctive characteristics of strategic models, and the process for refunding VAT paid for raw materials in export-oriented firms are all studied in this article. Also, scholarly debates are undertaken, and recommendations are made for enhancing tax control procedures in the export operation.